Assessing Groundwater Dynamics and Hydrological Processes in the Sand River Deposits of the Limpopo River, Mozambique - Saveca, Paulo Sérgio Lourenço; Abi, Attoumane; Stigter, Tibor Yvan; Lukas, Eelco; Fourie, Francois (Frontiers in Water, 2022)
Drought and water scarcity constrain the socioeconomic development of many (semi-)arid regions of Southern Africa. Moreover, due to the increase of water withdrawals upstream, the Limpopo River is no longer perennial in Mozambique. Fortunately, its river bed can store significant amounts of freshwater, because of the occurrence of thick and often coarse sand deposits formed through pronounced dryland weathering, erosion, and sedimentation in the river channel. Such so-called “sand rivers” exist in many parts of semi-arid Africa and have varying configurations and hydrological conditions. The current research aims to comparatively assess the Limpopo sand river aquifer in terms of recharge and discharge dynamics, storage potential, and interactions with the surface water flow, as a function of its specific hydrological conditions: its large size, location downstream of a dam releasing permanent ecological flow, and its relatively undeveloped state. For this purpose field investigations were carried out at two sites, involving groundwater level measurements, 2D geoelectrical surveying, water chemical and stable isotope analysis, and sediment classification. These investigations reveal the occurrence of medium to coarse sands with thicknesses that can reach 10–15 m, dropping to 2–5 m in the main river channel, underlain by less permeable clays and silts. Analysis of the river level shows that large parts of the sand river are flooded almost every year, providing optimal conditions for recurring and rapid recharge of the system (confirmed by infiltration tests) through two mechanisms: direct infiltration of surface runoff and lateral flow toward non-flooded areas of the river valley, also confirmed by the chemical and isotope study. During the dry season, groundwater provides base flow to the river and the average water level drop in the sand river system is about 1.8 m. The connectivity with the river margins is limited, due to the clayey nature of the river bank sediment, but local paleochannels can result in a continuation of sand layers. Hydrological processes controlling the water quality are evapoconcentration, mixing of discharging groundwater with the perennial surface water flow, and to a minor extent mineral dissolution, with the groundwater being of Ca-HCO3 type. The combination of the large size, high permeability, and frequent flooding of the sand river deposits provides optimal conditions for groundwater abstraction, requiring additional assessment of the impact on riparian vegetation and downstream users.